The Association between Exclusive Breastfeeding, Maternal Nutritional Status, Maternal Zinc Intake, and Stunting in Infants Aged 6 Months - Anindya, Ivanda Glanny; Salimo, Harsono; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2020)
Background: Stunting is a form of malnutrition that has an impact on decreased learning achie